2016
DOI: 10.7897/2277-4343.075201
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Immediate Release Tablets of Repaglinide by a Solubility Enhancer and Hot-Melt Extrusion Method

Abstract: To enhance the solubility of Repaglinide, we attempted to use Plasdone S 630, a novel solubility enhancer. Followed by the hot-melt extrusion method and made into a tablet dosage form. The prepared dosage forms subjected to all pre-compression and post-compression parameters evaluations. The data obtained from in-vitro drug release suggested that the trial-11 is the ideal formulation among all other formulations. The in-vitro release was also profiling around 95% within 45 minutes. The hardness of the prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Samples were removed after 1, 2 and 3 months and evaluated for % drug content and in vitro dissolution studies and compared with those results. [20] Preparation of Tenoxicam fast disintegrating tablets Twenty-seven formulations (TF1-TF27) for active layer were prepared by direct compression method using 3 3 Response surface method (3 variables and 3 levels of superdisintegrants) by using Design of experiment software with superdisintegrants like Gellan Gum, Fenugreek Seed Mucilage and L-HPC. All the formulations were varied in concentration of superdisintegrants, magnesium stearate constituted in all the formulations.…”
Section: Drug Contentmentioning
confidence: 99%
See 3 more Smart Citations
“…Samples were removed after 1, 2 and 3 months and evaluated for % drug content and in vitro dissolution studies and compared with those results. [20] Preparation of Tenoxicam fast disintegrating tablets Twenty-seven formulations (TF1-TF27) for active layer were prepared by direct compression method using 3 3 Response surface method (3 variables and 3 levels of superdisintegrants) by using Design of experiment software with superdisintegrants like Gellan Gum, Fenugreek Seed Mucilage and L-HPC. All the formulations were varied in concentration of superdisintegrants, magnesium stearate constituted in all the formulations.…”
Section: Drug Contentmentioning
confidence: 99%
“…The prepared tablets were subjected to dissolution studies. [21] Response surface methodology Study type: Response surface Design type: central composite Design mode: quadratic Twenty-seven formulations (TF1-TF27) were prepared by direct compression method using 3 3 Response surface method where 3 3 indicates 3 variables and 3 levels of superdisintegrants like Gellan Gum, Fenugreek Seed Mucilage and L-HPC (low, middle and high concentrations) by using Design of experiment software. [21][22] Pre-compression evaluation tests Preformulation studies: Prior to compression, solid dispersions were evaluated for their characteristic precompression parameters, such as bulk density, tapped density, Hausner ratio, Car's compressibility index and angle of repose.…”
Section: Drug Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of solid dispersions as a practically viable method to enhance the bioavailability of poorly water-soluble drugs to overcome the limitations of previous approaches such as salt formation, solubilization by co-solvents and particle size reduction studies revealed that drugs in solid dispersion need not necessarily exist in the micronized state. Eprosartan mesylate, chemically (E)-4-({2-Butyl-5-2-carboxy-2-(thiophene-2ylmethyl) eth-1-en-1-yl-1H-imidazol-1-yl} methyl) benzoic acid is an anti-hypertensive drug which prevents the vasoconstrictor and aldosteronesecreting effects of angiotensin II by selectively blocking the binding of angiotensin II to the AT1 receptor in vascular smooth muscle 1 .…”
mentioning
confidence: 99%